The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1111/j.1365-294x.2007.03406.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk of ectoparasitism and genetic diversity in a wild lesser kestrel population

Abstract: Parasites and infectious diseases are major determinants of population dynamics and adaptive processes, imposing fitness costs to their hosts and promoting genetic variation in natural populations. In the present study, we evaluate the role of individual genetic diversity on risk of parasitism by feather lice Degeeriella rufa in a wild lesser kestrel population (Falco naumanni). Genetic diversity at 11 microsatellite loci was associated with risk of parasitism by feather lice, with more heterozygous individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 86 publications
4
60
0
Order By: Relevance
“…We used two metrics to estimate individual genetic diversity: (i) uncorrected heterozygosity (H O ), calculated as the proportion of loci at which an individual is heterozygous and (ii) homozygosity by locus (HL), a microsatellite derived measure that improves heterozygosity estimates in open populations by weighting the contribution of each locus to the homozygosity value depending on its allelic variability (Aparicio et al 2006;Ortego et al 2007b). Particularly, HL improves heterozygosity estimates when markers are highly different in variability, as is the case in this study (Ortego et al 2007a;e.g. Ortego et al 2007c).…”
Section: (C) Immigration Patternsmentioning
confidence: 74%
See 2 more Smart Citations
“…We used two metrics to estimate individual genetic diversity: (i) uncorrected heterozygosity (H O ), calculated as the proportion of loci at which an individual is heterozygous and (ii) homozygosity by locus (HL), a microsatellite derived measure that improves heterozygosity estimates in open populations by weighting the contribution of each locus to the homozygosity value depending on its allelic variability (Aparicio et al 2006;Ortego et al 2007b). Particularly, HL improves heterozygosity estimates when markers are highly different in variability, as is the case in this study (Ortego et al 2007a;e.g. Ortego et al 2007c).…”
Section: (C) Immigration Patternsmentioning
confidence: 74%
“…During the years 2000-2006, we have studied a total of 37 breeding colonies clustered in two subpopulations separated by 30 km: 'Villacañ as' (39830 0 N, 3820 0 W; 17 colonies) and 'Consuegra' (39835 0 N, 3840 0 W; 6 colonies) subpopulations (figure 1). However, in spite of the low exchange of individuals between both subpopulations, Bayesian modelbased clustering analyses (STRUCTURE v. 2.1, Pritchard et al 2000) indicated that they are not genetically differentiated (maximum number of clusters modelledZ10; Ortego et al 2007aOrtego et al , 2008.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2010), driving genetic variation (Acevedo-Whitehouse et al 2003;Ortego et al 2007;Spurgin and Richardson 2010) and sexual selection (Hamilton and Zuk 1982). Understanding how patterns of pathogen-mediated selection vary across populations may therefore provide new insights into the mechanistic processes behind adaptation and natural selection.…”
Section: Introductionmentioning
confidence: 99%
“…Foerster et al 2003;Ortego et al 2007a), immunocompetence (e.g. Hawley et al 2005), parasite resistance (Acevedo-Whitehouse et al 2003;Ortego et al 2007b) and survival probability (e.g. Kruuk et al 2002;Van de Casteele et al 2003).…”
Section: Introductionmentioning
confidence: 99%